Assessment of the 24th Week Success of Anti-Retroviral Therapy in the Action against HIV in Istanbul Database: Results from a Region with Increasing Incidence - Bolukçu, Sibel; BOLUKÇU, SİBEL; METE, BİLGÜL; Gündüz, Alper; Karaosmanoglu, Hayat Kumbasar; Sargın, Fatma; DURDU, BÜLENT; DURDU, BÜLENT; Aydin, Ozlem Altuntas; Yildiz, Dilek; DÖKMETAŞ, İLYAS; Asian, Turan; et al. (My University, 2019)
We aimed to assess the 24-week virological and immunological success of the treatment of treatment-naive and treatment-experienced patients included in the Action against HIV in Istanbul (ACTHIV-IST) database. The ACTHIV-IST database was screened retrospectively from January 2012 to January 2014. The data for these patients such as age, sex, treatment-naive or treatment-experienced status, date of diagnosis, date of commencing antiretroviral therapy, antiretroviral therapy regimen, CD4+ cell count, and viral load before and after therapy were analyzed. In the 24th week of antiretroviral therapy, there were 40 (17.9%) and 29 (14.1%) virological and immunological failures, respectively. Virological failure (VF) was associated with a baseline viral load > 100,000 copies (p = 0.004). A CD4+ cell count lower than 200 cells/µl was not found to be associated with VF (p = 0.843). Immunological failure was substantially rare in patients with a baseline CD4+ cell count > 200 cells/µl (p = 0.005). Although an HIV-RNA 侑 100,000 copies/ml was protective against VF in the 24th week, in individuals with an HIV-RNA > 100,000 copies/ml, VF was 3.2 times more likely to occur. Baseline VF was the most predictive parameter to estimate 24th week virological success and VF. VF is an important prognostic parameter resulting in CD4+ cell depletion, AIDS-related events, and increased mortality.